2020
DOI: 10.1038/s41590-019-0578-8
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide CRISPR–Cas9 screening reveals ubiquitous T cell cancer targeting via the monomorphic MHC class I-related protein MR1

Abstract: Users may view, print, copy, and download text and data-mine the content in such documents, for the purposes of academic research, subject always to the full Conditions of use:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
226
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 222 publications
(250 citation statements)
references
References 38 publications
3
226
1
Order By: Relevance
“…TLR agonists have shown synergies and abrogation of suppressive states in vitro [92,93], and cytokines, such as IL-2, could be explored further to evaluate their synergistic effects on effector cell activation and expansion. On the other side, sensory pathways are being discovered which might give additional or alternative therapeutic angles, such as the recently identified MR-1 specific cancer-selective TCR clone [169]. Finally, while there are many hurdles to be jumped, γδ T cells with their high plasticity [27] represent a potential therapeutic option for a significant patient population with solid tumors.…”
Section: Perspectivementioning
confidence: 99%
“…TLR agonists have shown synergies and abrogation of suppressive states in vitro [92,93], and cytokines, such as IL-2, could be explored further to evaluate their synergistic effects on effector cell activation and expansion. On the other side, sensory pathways are being discovered which might give additional or alternative therapeutic angles, such as the recently identified MR-1 specific cancer-selective TCR clone [169]. Finally, while there are many hurdles to be jumped, γδ T cells with their high plasticity [27] represent a potential therapeutic option for a significant patient population with solid tumors.…”
Section: Perspectivementioning
confidence: 99%
“…Unlike classical MHC I, MR1 is not polymorphic in the population and it presents small non-peptidic antigens such as metabolites [42]. A recent study suggests that such MR1-mediated presentation of the metabolome of cancer cells is utilized by specific T cells for ubiquitous cancer targeting [43].…”
Section: Discussionmentioning
confidence: 99%
“…They observed regression of leukaemia and prolonged survival of mice. Moreover, Crowther et al demonstrated in in vitro experiments that T cells of melanoma patients transduced with identified TCR could effectively kill not only the patient's own cancer cells, but also non-autologous melanoma cells [159]. These data suggest that the MR1-restricted TCR, recognises diverse types of tumours irrespective of MHC and thus may open the opportunity for a pan-cancer T cell-based therap.…”
Section: Mr1-restricted T Cells-a Novel Population Of T Cells With Pamentioning
confidence: 99%
“…Very recently Crowther and colleagues published results that opened an exciting prospect of potential use of MR1-restricted T cells in immune therapy not limited by MHC polymorphism [159].…”
Section: Mr1-restricted T Cells-a Novel Population Of T Cells With Pamentioning
confidence: 99%
See 1 more Smart Citation